1999
DOI: 10.1002/(sici)1096-8628(19991105)87:1<53::aid-ajmg11>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of angiotensinogen gene in molecular basis of human hypertension: Sibpair linkage and association analyses in Australian Anglo-Caucasians

Abstract: Linkage with essential hypertension has been claimed for a microsatellite marker near the angiotensinogen gene (AGT; chromosome 1q42), as has association for the AGT variants M235T, G(-6)A and A(-20)C. To more rigorously evaluate AGT as a candidate gene for hypertension we performed sibpair analysis with multiple microsatellite markers surrounding this locus and using more sophisticated analysis programs. We also performed an association study of the AGT variants in unrelated subjects with a strong family hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 53 publications
0
18
2
1
Order By: Relevance
“…These findings stress the necessity of considering ethnic factors in the assessment of genetic risk identifiers. Also Wang et al, 19 have reported controversial results with AGT gene in a hypertensive Australian population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings stress the necessity of considering ethnic factors in the assessment of genetic risk identifiers. Also Wang et al, 19 have reported controversial results with AGT gene in a hypertensive Australian population.…”
Section: Discussionmentioning
confidence: 99%
“…33 An absence of association has been observed in Africans, 14,16 in Chinese 34,35 and in the Australian population. 19 In the meta-analysis of Kunz et al, 10 which includes 5493 patients, carried out in a white population, the estimated associated risk to the allele 235T was 1.2 (95% Cl, 1.11 to 1.29; P Ïœ 0.0001). The risk increased when we considered the family history of AH or the AH was stratified, but different bias were also reported in the studies analysed which reflected, for example, defects in their selection of the sample size or lack of homogeneity in the population studied.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…The A-6G polymorphism located in the promoter region of the AGT gene was analyzed using the method described by Wang et al 27 The 3 0 promoter region was amplified with oligonucleotides 5 0 -GAG GTC CCA GCG TGA GTG TCG C and 5 0 -CTC AGT TAC ATC CTG AGA GAG ACA AGA CC under standard PCR conditions. Fragments were analyzed by SSCP using water-cooled vertical minigels (10 Â 10 cm 2 ).…”
Section: Analysis Of Polymorphisms (Ace I/d A-6g A1166c and C573t)mentioning
confidence: 99%
“…Ten publications were included in the final meta-analysis (Ishigami et al, 1997;Wang et al, 1999;Sato et al, 2000;Tsai et al, 2003;Velez et al, 2006;Niu et al, 2007;Qi et al, 2008;Jiang et al, 2009;Ying et al, 2010;Li et al, 2013) based on the above-mentioned inclusion and exclusion criteria. Details of the selection process are presented in the flow chart in Figure 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%